THE FACTORS AFFECTING ACCOUNTING CONSERVATISM IN LISTED INDONESIAN MANUFACTURING COMPANIES - Sasya Sabrina, Jessica Elvina (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study analyses the factors affecting accounting conservatism. The factors included in this study are bonus plan, debt covenant, growth opportunity, and litigation risk. The sample is manufacturing companies listed on the Indonesian Stock Exchange that published an audited financial report for the 2013-2015 period. The 156 points of data were collected based on purposive sampling from 52 manufacturing companies in Indonesia and were analysed using multiple linear regressions. The study concluded that debt covenant has a positive effect on accounting conservatism, growth opportunity has a positive effect on accounting conservatism, bonus plan has no effect on accounting conservatism, and litigation risk has no effect on accounting conservatism.